2021
DOI: 10.7150/thno.51478
|View full text |Cite
|
Sign up to set email alerts
|

Bruceantin targets HSP90 to overcome resistance to hormone therapy in castration-resistant prostate cancer

Abstract: Rationale: Aberrant androgen receptor (AR) signaling via full-length AR (AR-FL) and constitutively active AR variant 7 (AR-V7) plays a key role in the development of castration-resistant prostate cancer (CRPC) and resistance to hormone therapies. Simultaneous targeting of AR-FL and AR-V7 may be a promising strategy to overcome resistance to hormone therapy. This study aimed to identify novel drug candidates co-targeting AR-FL and AR-V7 activities and elucidate their molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…In addition, BD has been found to inhibit hepatocellular carcinoma by inhibiting signaling pathways related to liver carcinogenesis and disease progression [ 35 ]. Quassinoids are typically more potent than fatty acids, with 50% inhibitory concentration (IC 50 ) values down to the nanomolar level [ 37 ], and hence most therapeutic focus has been on quassinoids [ 38 , 39 ].…”
Section: Overview Of Brucea Javanica Oil and Momentioning
confidence: 99%
“…In addition, BD has been found to inhibit hepatocellular carcinoma by inhibiting signaling pathways related to liver carcinogenesis and disease progression [ 35 ]. Quassinoids are typically more potent than fatty acids, with 50% inhibitory concentration (IC 50 ) values down to the nanomolar level [ 37 ], and hence most therapeutic focus has been on quassinoids [ 38 , 39 ].…”
Section: Overview Of Brucea Javanica Oil and Momentioning
confidence: 99%
“…Unfortunately, the regulatory mechanisms underlie CRPC development remains elusive. Various studies have been demonstrated that reactivation of AR that resulted from the genetic mutation and amplification, increased stability, and expressions of splice variants, may be the major mechanism that contributes to the progress from the androgen-dependent PC to CRPC 4 , 26 , 33 - 35 . Our previous study demonstrated a novel mechanism that SIX1 signal can also contribute to the progression of CRPC 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 inhibitors also act synergistically with many other anticancer therapies, including photodynamic therapy (PDT) [ 117 ] and hormone therapy [ 118 , 119 , 120 ], via different mechanisms. Furthermore, some bifunctional drugs, such as STA-8666 (HSP90 inhibitor and topoisomerase inhibitor SN-38) [ 121 ], DHP1808 (HSP90-PI3K) [ 122 ] and MPT0G449, are essentially in combination.…”
Section: Hsp90 Combination Therapymentioning
confidence: 99%